Motivasi pembelajaran kemahiran mendengar Bahasa Arab dan hubungannya dengan pencapaian pelajar - Nik Mohd Rahimi Nik Yusoff; Zamri Mahamod; Kamarulzaman AB. Ghani (penerbit ukm, 2008)
The aims of this study are: (1) To identify the level of motivation in learning Arabic listening skills, (2) To identify the level of Arabic listening skills, (3) To identify the relationship between motivation and Arabic listening skills, and (4) To identify the differences between three group, namely high, moderate, and low motivation. This study used the cross sectional research design and employed two research instruments to collect the data, namely questionnaire and Arabic listening test. The results showed: (a) the motivation at the high level, (b) the Arabic listening skills at the moderate level, (c) there was asignificant relationships between motivation and Arabic listening skills, and (d) there was a significant differences between the three group.